2018
DOI: 10.1007/s00428-018-2366-5
|View full text |Cite
|
Sign up to set email alerts
|

c-MYC amplification and c-myc protein expression in pancreatic acinar cell carcinomas. New insights into the molecular signature of these rare cancers

Abstract: The molecular alterations of pancreatic acinar cell carcinomas (ACCs) and mixed acinar-neuroendocrine carcinomas (MANECs) are not completely understood, and the possible role of c-MYC amplification in tumor development, progression, and prognosis is not known. We have investigated c-MYC gene amplification in a series of 35 ACCs and 4 MANECs to evaluate its frequency and a possible prognostic role. Gene amplification was investigated using interphasic fluorescence in situ hybridization analysis simultaneously h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…The 8q24 amplification was found in two of seven (28.57%) in LGD, one of 17 (5.88%) in HGD, six of 11 (54.55%) in INC ( P = 0.011). MYC is located in the 8q24 amplified regions in IPMNs (Table ), which is one of the most frequently altered genes by CNAs in pan‐cancer analysis and whose amplification has been found in pancreatic acinar cell carcinomas . The deletion region 17p13, which contains TP53 (Table ) was also found to co‐occur with TP53 point mutations in all of the malignant samples (INC) with TP53 mutations (Figure D), which might be consistent with the two‐hit theory of tumor suppressor genes.…”
Section: Resultssupporting
confidence: 74%
“…The 8q24 amplification was found in two of seven (28.57%) in LGD, one of 17 (5.88%) in HGD, six of 11 (54.55%) in INC ( P = 0.011). MYC is located in the 8q24 amplified regions in IPMNs (Table ), which is one of the most frequently altered genes by CNAs in pan‐cancer analysis and whose amplification has been found in pancreatic acinar cell carcinomas . The deletion region 17p13, which contains TP53 (Table ) was also found to co‐occur with TP53 point mutations in all of the malignant samples (INC) with TP53 mutations (Figure D), which might be consistent with the two‐hit theory of tumor suppressor genes.…”
Section: Resultssupporting
confidence: 74%
“…The histology of the non-neuroendocrine component was reported in 74 studies (n = 606) [11][12][13]64,65,68,[72][73][74][75][79][80][81][82][84][85][86][87]89,[91][92][93][95][96][97]101], and was consistent with an adenocarcinoma in 92.2% of cases (n = 559) (acinar cell carcinoma in 7.6% (n = 46)), an adenoma in 4.5% (n = 27), a squamous cell carcinoma in 2.5% (n = 15), a hepatocellular carcinoma in < 1% (n = 1), and a mixture of an adenocarcinoma and a squamous cell carcinoma in < 1% (n = 4). The grade of differentiation of the non-neuroendocrine component was specified in 38 studies (n = 124), and was well differentiated in 24.2% (n = 30), moderately differentiated in 35.5% (n = 44), and poorly differentiated in 39.5% (n = 49).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
“…Twenty studies (n = 381) reported on the genetic/molecular alterations underlying MiNEN [29,30,35,58,59,64,67,71,72,77,79,81,82,85,89,[91][92][93]95,97]. In 49.1% of cases where genetic/molecular data was available, the site of origin of MiNEN was the colon-rectum.…”
Section: The Molecular Landscape Of Minen and Pathogenetic Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations